Helicobacter pylori-negative Gastric Mucosa-associated Lymphoid Tissue Lymphoma - Jin Tae Jung (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Approximately 90% of gastric mucosa-associated lymphoid tissue (MALT) lymphomas are associated with Helicobacter pylori infection and 10% of gastric MALT lymphomas occur independent of H. pylori infection. The gene translocation t(11;18)(q21;q21) is frequently observed in cases presenting with H. pylori-negative gastric MALT lymphomas. H. pylori-negative gastric MALT lymphomas do not differ from H. pylori-positive gastric MALT lymphomas in terms of clinical features and endoscopic findings and show similar prognosis. H. pylori eradication therapy could be considered as first-line treatment for gastric MALT lymphomas regardless of their H. pylori infection status. In cases with H. pylori-negative gastric MALT lymphomas, the rate of response to eradication therapy varies from 0 to 83%. If gastric MALT lymphoma persists for more than a year, secondary treatment with radiotherapy, chemotherapy, and/or surgery should be considered. Of note, the comparative outcome is excellent.